Catalog of Nabidae (Hemiptera: Heteroptera) for the Neotropical Region - Volpi, Lorena Noeli (2010)
The Nabidae (Hemiptera) of the Neotropical Region are cataloged. A total of 12 genera and 83 species are listed together with their synonyms. References are given to the original descriptions and the subsequent taxonomic position, the location of types, and the geographic distribution. A comprehensive bibliography is provided.